Affirmative actions: Polemics and Possibility about Racial Equality and the Role of the State - Santos, Sales Augusto dos; Cavalleiro, Eliane; Barbosa, Maria Inês; Ribeiro, Matilde (Revista Estudos Feministas, 2008)
The article analyses the importance of the role of the State for the implementation ofpublic policies of affirmative action, especially for black students to enter public higher education.It argues that affirmative action is one of the alternatives to reduce or minimize the inequality inthis field between black and white students and/or students from public schools and privateschools, in particular by means of one of its techniques of implementation: the quota system. Inspite of there being various arguments against the quota system, the authors concentrate ondebating or counter-arguing only one: that the quota system may generate racial conflicts inBrazil.